FULLTEXT : e-Proceedings: The 9th International Islamic Economic System Conference (I-iECONS 2021) - Suhaila Abdul Hamid; Agoos Munalis Tahir; Nor Haziah Hashim; Nur Ainna Ramli; Hartini Mohammad; Abdullah Mohammed Ahmed Ayedh; Muhammad Azrin Nazri (Universiti Sains Islam Malaysian, 2024)
e-Proceedings: The 9th International Islamic Economic System Conference (I-iECONS 2021) 12th – 13th July 2021, Malaysia"